1988
DOI: 10.1111/j.1365-3024.1988.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological characteristics of the glutathione S‐transferases of Schistosoma japonicum and Schistosoma mansoni

Abstract: When aqueous extracts of Schistosoma japonicum and S. mansoni adult worms are passed over columns of glutathione-conjugated agarose, two molecular species of Mr 26,000 and Mr 28,000 are detected in eluates as analysed by SDS-PAGE, these eluates having glutathione S-transferase (GST) activity. The molecules, termed Sj26 and Sj28 from S. japonicum and Sm26 and Sm28 from S. mansoni, can be immunogenic in rabbits or mice and appear not to be linked together as subunits of GST heterodimers. The elution profile of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Mice vaccinated with DNA that contained the SmCT-SOD gene seemed to react with GST (Fig. 4D), although previous reports showed that there was no cross-reactivity between the S. japonicum (Sj26) GST and the S. mansoni counterpart in mice (28,64). However, as this reactivity occurred only at a very low titer (1:80), we considered such reactivity irrelevant in our study.…”
Section: Discussionmentioning
confidence: 84%
“…Mice vaccinated with DNA that contained the SmCT-SOD gene seemed to react with GST (Fig. 4D), although previous reports showed that there was no cross-reactivity between the S. japonicum (Sj26) GST and the S. mansoni counterpart in mice (28,64). However, as this reactivity occurred only at a very low titer (1:80), we considered such reactivity irrelevant in our study.…”
Section: Discussionmentioning
confidence: 84%
“…Mention should be made that neither Iodogen nor Chloramine T methods were able to label these proteins. The reason remains unknown but this observation could be related to the work of Tiu et al (1988) who reported similar results concerning the Schistosoma japonicum 26 kDa G S T . This might be due not to an absence of tyrosine in the molecules but rather to the non-accessibility of such residues during labelling.…”
Section: Immunogenicity Of Tcgbp During Human and Experimental Chagasmentioning
confidence: 75%
“…A 26 KDa isoenzyme of S.japonicum glutathione S-transferase (Sj26GST), which catalyses detoxification of lipophilic molecules by thioconjugation, is one of the six antigens recommended by WHO for vaccine development [24]. It has been shown that the reduction of worm burdens and liver egg numbers in mice can reach 30.1% and 44.8%, respectively, after immunization with a plasmid containing Sj26GST DNA (pVAX1-Sj26GST) [25].…”
Section: Introductionmentioning
confidence: 99%